Haemogloin Level, Blood Group, Chest X Ray Findings and Consanguinity in Thalassemic Children in AL Muthana Governorate - Abid, Fadil Abass (AL-Kindy College Medical Journal, 2013)
Background: Thalassemia is characterized by the decrease or absence of the synthesis of one or more globin chains of hemoglobin. Thalassemia is distributed worldwide and is characterized by; regular blood transfusion which is creating alloimmunization to erythrocyte antigens is one of the major complications of regular blood transfusions in thalassemia, particularly in patients who are chronically transfused.Objectives: The aims of this study are to understand the immune system profile as the triggering factor for thalassemia.Methods: Thirty patients aging between one year and four months and twenty two years, twenty two of them were boys and eight were girls. Twenty nine patients, their parents are relative except one and studied in the maternity and Children teaching Hospital of Al Samawa city. Belonging to Blood groups O+, B+, A+, O- and B- , showed,12,8,7,2 and 1 patients respectively compared to control group 30 persons with no relation to blood groups. High percentages of relative marriages as seen in my study (96.66%), from all Al muthana population how were visiting the hospital during 2010, in thalassemic center. Results: twenty six patients out of thirty patients studied suffer from cardiomegaly (86.66%) due to iron over load because of frequent blood transfusion and immune system disorder. Results also showed eight patients suffer also from Bronchopneumia (26.66%) and all patients had hepatomegaly, splenomegaly and hemoglobin were low in all patients compared to hemoglobin control average which was 10.72-14.76 g/dl. Facial and teeth deformities were recognized in twenty six patients (86.66%).Conclusions: hepatomegaly and splenomegaly, followed by cardiomegaly, facial and teeth deformities were the most persistently recognized features in thalassemic patients. Bronchopneumia is less frequent but not uncommon.